2008
DOI: 10.1007/s12192-008-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of chaperonin containing T-complex polypeptide (CCT) subunits during fetal and adult skin wound healing

Abstract: Integumentary wound healing in early fetal life is regenerative and proceeds without scar formation. Expressomic analysis of this phenomenon by differential display has previously determined that the eta subunit of the cytosolic chaperonin containing T-complex polypeptide (CCT) is downregulated in the healing fetal wound milieu. We now report that no other CCT subunit shares this distinct pattern of gene regulation as determined by limiting dilution reverse transcriptase polymerase chain reaction (RT-PCR); all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 22 publications
2
25
2
Order By: Relevance
“…1). These results are somewhat at variance with our observations from adult cutaneous wounds at a similar time point; in skin wounds, CCT-alpha is reduced, while CCT-beta remains invariant (Satish et al 2008).…”
Section: Genescontrasting
confidence: 63%
See 4 more Smart Citations
“…1). These results are somewhat at variance with our observations from adult cutaneous wounds at a similar time point; in skin wounds, CCT-alpha is reduced, while CCT-beta remains invariant (Satish et al 2008).…”
Section: Genescontrasting
confidence: 63%
“…We noted that no other chaperonin subunits share this specific pattern of downregulation at the tissue level (Satish et al 2008), and have further observed that fibroblasts from fetal skin tissues express substantially less CCT-eta mRNA than do fibroblasts from adult skin (Satish et al 2010a, b). These observations led us to investigate the pattern of CCT subunit expression in mucosal tissues and fibroblasts to see if comparable patterns would emerge.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations